Case report: Persistent COVID-19 in a patient with B cell lymphoma refractory to antiviral treatment due to resistance to Remdesivir - Luiz Eduardo Ceccon Calil de Assumpção; Bruno Graciano Ponce Romeo; João Carlos de Campos Guerra; Luis Fernando Aranha Camargo; Marcelo Akira Nagaoka; Deyvid Emanuel Amgarten; Erick Gustavo Dorlass; Roberta Cardoso Petroni; Afonso Celso Almeida Cardoso; Renato de Mello Ruiz; Carolina Devite Bittante; Vanessa Damazio Teich; et al. (IDCases)
Background: There is a significant concern of the pandemic impact of SARS-CoV-2 infection in immunocompromised patients. These patients can develop long COVID-19 due to impairment of cellular and humoral immunity. On the other hand, prolonged infection can lead to mutations in the SARS CoV-2 genome that can impact on the resistance to antiviral therapy. Remdesivir cases have been reported in patients receiving antiviral drug treatment. Case presentation: A 46-year-old male with previous mantle cell lymphoma resolved by autologous bone marrow transplantation without other comorbidities had SARS-CoV-2 detected in February 2022 and received the recommended antiviral treatment with Remdesivir. COVID-19 evolved in four months with worsening of the symptoms, despite an initial rapid improvements and high RT-PCR Ct values. The patient was relieved from hospital care stable and well but still maintaining positive test results. Conclusions: the patient presented prolonged COVID-19 with persistence of virus detected by RT-PCR for several months. The strain sequenced presented a mutation different from all reported previously. Although it was no possible to sequence the initial strain without these mutations, our data suggests that immunocompromised patient with prolonged COVID-19 may serve as reservoir for strains of SARS-CoV-2 with resistant components in his genome.